Status of dyslipidemia management and statin undertreatment in Korean cancer survivors: A Korean National Health and Nutrition Examination Survey study. (24th February 2020) - Shin, Sujeong; Wook Shin, Dong; Young Cho, In; Jeong, Su-Min; Jung, Hyein
Abstract: Aims: Due to improving cancer treatment results, non-cancer mortality is an important issue for cancer survivors. Cardiovascular diseases are the leading causes of death in Korea and globally. In addition to lowering the risk of cardiovascular disease, the use of statins has led to an overall reduction in cancer mortality in recent observational studies. We investigated the status of current dyslipidemia management in cancer survivors with reference to 2018 guidelines. Methods: The study is a cross-sectional analysis of 1460 cancer survivors aged from 40 to 75 years who participated in the Korean National Health and Nutrition Examination Survey from 2007 to 2016. Dyslipidemia management status among cancer survivors was assessed according to 2018 American College of Cardiology/American Heart Association guidelines and Korean Coronary Heart Disease Risk Score guidelines. Results: The rate of treatment for dyslipidemia was 8.5% for males, 13.8% for females, and 11.9% overall. Among cancer survivors who were not receiving treatment for dyslipidemia, 59.6% of males, 34.2% of females and 43.9% of total cancer survivors would have been eligible for statin therapy under the 2018 American College of Cardiology/American Heart Association guidelines and Korean Coronary Heart Disease Risk Score guidelines. The rate of undertreatment of dyslipidemia increased with age and length of time since cancer diagnosis. Conclusion: Nearly 50% of cancer survivors remain untreated although they are eligible for statin therapy. This emphasizes the need for more attention to prevent atherosclerotic cardiovascular disease among cancer survivors.